Battle of the Reichswald - Elstob, Peter; Editor-in-Chief: Pitt, Barrie (New York Ballantine Books, 1970)
The story of some of the difficulties the Allies encountered trying go repel the Germans back inside their borders.
Include Illustrations, Figures, Maps and Bibliography.
Keywords: Reichswald, Battle of the (Germany : 1945) -- Germany